QUANTIFICAÇÃO DE METAIS E METALOIDES EM TINTA DE CABELOS E AVALIAÇÃO DO POTENCIAL RISCO A SAÚDE - Gelson Martins da Silva (2023)
People find ways to express cultural values and feelings through hair colors. In the coloring process, some risks may go unnoticed since there are chemical elements such as heavy metals, which, depending on the level of exposure, can generate toxicity capable of inducing oxidative stress via the formation of free radicals. Given the above, this work aimed to quantify the concentrations of heavy metals and metalloids obtained in tinctures from different Brazilian manufacturers and an international sample. An acid digestion procedure for the hair dye samples was performed, and then quantification of the elements using coupled plasma optical emission spectrometry. Risk calculations of possible exposure from the calculation of cutaneous absorption of potentially harmful elements in particles adhered to exposed skin (Ddermal) were performed considering an adult aged 40 years. A total of 14 elements were quantified in the paint samples, namely Al, Fe, Cr, Mg, As, Mn, Cu, Ba, Ni, Sr, Cd, Mo, As, and Pb. About all samples, elements Al and Fe have the highest concentration. According to the principal component analysis, the most significant trend of quantified elements is focused on samples M1 and M6. In addition, the risk quotient (HQ) and hazard index (HI) are < 1, causing no potential health risk within the studied exposure period. However, carcinogenic risk (CR) values ranged from 10−6 to 10−5. Therefore, the estimated risk is considered low.